Analisis Implementasi Proyek Penguatan Profil Pelajar Pancasila Di SMK Muhammadiyah 01 Pandaan - Pasuruan - Zuriah, Nurul; Sunaryo, Hari; Triyanto, Triyanto (University of Muhammadiyah Malang, 2024)
The research aims to analyze and describe the results of the study on the implementation of the Pancasila student profile strengthening project, the flow of determination in selecting the elements and sub-elements of the Pancasila student profile as well as the implementation of the Pancasila student profile strengthening project and work culture in the independent curriculum at SMK Muhammadiyah 01 Pandaan, Pasuruan. The research was carried out using a qualitative descriptive method, data collection was carried out by interviews, observations, and documentation studies. Data analysis is carried out, through four steps: transcription, coding, theme analysis, interpretation. The results of the study show that the Implementation of the Project to Strengthen the Pancasila Student Profile and Work Culture at SMK Muhammadiyah 01 Pandaan Pasuruan has made a great contribution in forming a Student Profile with Pancasila character. Some of the best practices identified in this study include the integration of Pancasila values in the curriculum, active participation of students, and the important role of teachers in shaping a quality work culture. There are several factors that affect the success of this project, including the support from the school, the involvement of students, and the teaching methods used. Research contributes to the development of character education and curriculum improvement in schools. The implications of this research can also be a reference for other schools in developing a strong Pancasila student profile and implementing a project to strengthen the Pancasila student profile and an effective work culture.